Transmission technology: signals for the next century. (4th August 2014) - Baur, Hans
Transmission technology is on the threshold of a new era: bit rates are rapidly increasing, and network structures are becoming more flexible and economic. Driving this evolutionary process are accelerating innovation cycles in microelectronics and advances in digital transmission technology and fibre optics. This article examines these events in the context of market forces.